2001
DOI: 10.1053/rmed.2001.1108
|View full text |Cite
|
Sign up to set email alerts
|

p53, p21 and metallothionein immunoreactivities in patients with malignant pleural mesothelioma: correlations with the epidemiological features and prognosis of mesotheliomas with environmental asbestos exposure

Abstract: The aim of this study is to investigate immunoreactivity for p53, p21 and metallothionein in diffuse malignant pleural mesothelioma (DMPM) and to determine the relationships between the age, sex, asbestos exposure time, survival of DMPM patients with environmental asbestos exposure and immunoreactivity to p53, p21 and metallothionein. Sixty-seven histopathologically-confirmed DMPMs, 38 of whom had environmental and 29 had occupational asbestos exposure, were included. The tumour tissue samples were immunostain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…17 18 However, p21 and p27 have also been shown to have a significant role in the Cumulative survival progression of human mesothelioma. [20][21][22] Interestingly, while p53 overexpression is a common event in mesothelioma, 24 it is rarely mutated or inactivated. 29 The data presented here showing COX-2 expression as the strongest predictor of a poor outcome not only confirm previous published results but also shed new light on the role of COX-2 in the pathogenesis and progression of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 18 However, p21 and p27 have also been shown to have a significant role in the Cumulative survival progression of human mesothelioma. [20][21][22] Interestingly, while p53 overexpression is a common event in mesothelioma, 24 it is rarely mutated or inactivated. 29 The data presented here showing COX-2 expression as the strongest predictor of a poor outcome not only confirm previous published results but also shed new light on the role of COX-2 in the pathogenesis and progression of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…18 It has been proposed that COX-2 exerts its influence on mesangial cell proliferation in vitro by a novel mechanism involving the tumour suppressor p53 and the cell cycle inhibitors p21 and p27, 19 and several recent studies have investigated the potential prognostic value of p53, p21 and p27 in malignant mesotheliomas. [20][21][22][23][24] A study was undertaken to analyse the potential prognostic value of the immunohistochemical expression of COX-2 and p27 in 29 malignant mesotheliomas already screened for the expression of p21 and p53 23 24 and for the presence of SV40-like sequences. 25 The correlation with survival of each factor in univariate and multivariate analysis was assessed.…”
mentioning
confidence: 99%
“…In a similar manner, the p21 CDK inhibitor has also been found to be differentially expressed in malignant mesothelioma [34,35]. Expression of p21 was initially identified as a protein that was up-regulated by expression of wild type p53 [36].…”
Section: Other Cdk Inhibitors: P27 and P21mentioning
confidence: 99%
“…In contrast, cancer cells with a defective p21 response undergo cell death that occurs during or after mitosis (8). Previous studies (9) showed that MPM expresses wild-type p21, with a frequency of >35%. In addition, unlike other malignancies, genetic alterations in p53 are rare and gene mutations in the p16…”
mentioning
confidence: 94%